Medical Management of Three Patients with an Acute Type A Aortic Dissection: Case Series and a Review of the Literature - Salhab, Khaled; Gioia, William; Rabenstein, Andrew P.; Gubernikoff, George; Schubach, Scott (AORTA, 2018)
The model of surgery first and always for Type A aortic dissections has continued to evolve. During the last three decades, various studies have demonstrated that in select patients, surgery should be delayed or avoided. This case series examines three cases in which patients were medically treated. Furthermore, we review the literature and when surgery should be delayed for acute Type A aortic dissections.
Keywords: aortic dissection; Type A aortic dissection; ascending aorta